Active control of noise and vibration - Hansen, Colin H. (E. & F.N. Spon, 1997)
This major work is the first to treat the active control of both sound and vibration in a unified way. It outlines the fundamental concepts, explains how a reliable and stable system can be designed and implemented, and details the pitfalls . It covers sound in ducts, sound radiation, sound transmission into enclosures, structural vibration and isolation, electronic control system design, and sensors and actuators.